Evidence map of pancreatic surgery - a living systematic review with meta-analyses by the International Study Group of Pancreatic Surgery (ISGPS) - Probst, Pascal; Hüttner, Felix; Meydan, Ömer; Abu Hilal, Mohammed; Adham, Mustapha; Barreto, Savio G.; Besselink, Marc G.; Busch, Olivier R.; Bockhorn, Maximilian; Del Chiaro, Marco; Conlon, Kevin; Castillo, Carlos Fernandez-del; et al. (Surgery, 2021)
Background - Pancreatic surgery is associated with considerable morbidity and, consequently, offers a large and complex field for research. To prioritize relevant future scientific projects, it is of utmost importance to identify existing evidence and uncover research gaps. Thus, the aim of this project was to create a systematic and living Evidence Map of Pancreatic Surgery. - Methods - PubMed, the Cochrane Central Register of Controlled Trials, and Web of Science were systematically searched for all randomized controlled trials and systematic reviews on pancreatic surgery. Outcomes from every existing randomized controlled trial were extracted, and trial quality was assessed. Systematic reviews were used to identify an absence of randomized controlled trials. Randomized controlled trials and systematic reviews on identical subjects were grouped according to research topics. A web-based evidence map modeled after a mind map was created to visualize existing evidence. Meta-analyses of specific outcomes of pancreatic surgery were performed for all research topics with more than 3 randomized controlled trials. For partial pancreatoduodenectomy and distal pancreatectomy, pooled benchmarks for outcomes were calculated with a 99% confidence interval. The evidence map undergoes regular updates. - Results - Out of 30,860 articles reviewed, 328 randomized controlled trials on 35,600 patients and 332 systematic reviews were included and grouped into 76 research topics. Most randomized controlled trials were from Europe (46%) and most systematic reviews were from Asia (51%). A living meta-analysis of 21 out of 76 research topics (28%) was performed and included in the web-based evidence map. Evidence gaps were identified in 11 out of 76 research topics (14%). The benchmark for mortality was 2% (99% confidence interval: 1%-2%) for partial pancreatoduodenectomy and <1% (99% confidence interval: 0%-1%) for distal pancreatectomy. The benchmark for overall complications was 53% (99%confidence interval: 46%-61%) for partial pancreatoduodenectomy and 59% (99% confidence interval: 44%-80%) for distal pancreatectomy. - Conclusion - The International Study Group of Pancreatic Surgery Evidence Map of Pancreatic Surgery, which is freely accessible via www.evidencemap.surgery and as a mobile phone app, provides a regularly updated overview of the available literature displayed in an intuitive fashion. Clinical decision making and evidence-based patient information are supported by the primary data provided, as well as by living meta-analyses. Researchers can use the systematic literature search and processed data for their own projects, and funding bodies can base their research priorities on evidence gaps that the map uncovers.
Gesehen am 16.12.2021